A nacre protein forms mesoscale hydrogels that "hijack" the biomineralization process within a seawater environment - Pendola, M.; Jain, G.; Davidyants, A.; Huang, Y.; Gebauer, Denis; Evans, J. (The Royal Society of Chemistry, 2016)
This journal is © 2016 The Royal Society of Chemistry.We examined the mineralization performance of a nacre protein, AP7, within seawater mineralization assays that form aragonite and magnesium calcite. Under these conditions AP7 forms hydrogel particles that vary in size and complexity depending upon ionic conditions. These hydrogels "hijack" the mineralization process by limiting nucleation in bulk solution and promoting nucleation within the hydrogels.